Sign language interpreting and interpreter education : directions for research and practice - Marschark, Marc (Perspectives on deafness., 2005)
This text provides an overview of the field of sign language interpreting and interpreter education, including evaluation of the extent to which current practices are supported by research, and will be of use both as a reference book and as a textbook for interpreter training programmes.